PSYCHOHISTORY DALAM KAJIAN SELF-ESTEEM TEKS DEKLARASI NU 1983 TENTANG HUBUNGAN PANCASILA DAN ISLAM - Robit Nurul Jamil; Hermanu Joebagio; Djono Djono (Jurnal Theologia, 2018)
Special concern on the sources of Islamic history contributes to the thoughts and identity of Indonesian Muslims. Muslim self-esteem can be formed from these historical sources. The formation of Muslim self-esteem gives the right decision so that it does not come out of the context of religion and humanity. The historical source used in this study is the text of the 1983 Nahdlatul Ulama Declaration (NU). The concept of Islam Nusantara (NU) 2015 is an implication of the values of the text of the declaration. The purpose of this study is to provide new insights regarding the 2015 NU's concept of Islam Nusantara by analyzing the historical sources of the text of the 1983 NU Declaration and exploring the values of self-esteem contained in the text of the declaration. The study used a qualitative method with psychohistory approach. This study produced two discussions: 1) The 2015 NU's concept of Islam Nusantara. 2) Psychohistory self-esteem in the historical source of the text of the 1983 NU Declaration. This study concluded that the conception of Islam Nusantara 2015 was mandated by the 1983 NU declaration, in its implementation provides Islamic self-esteem that can hinder the process of radicalization.